Conflict and communication gap among the critical care nurses during care of patients with COVID-19 - Shereen Abd El-Moneam Ahmed; Samia Gaballah (Elsevier, 2023)
Background: COVID-19 overwhelmed many countries' healthcare systems causing high levels of conflict amongst frontlines nurses. Aim: Explore the conflict level and communication gap among the critical care nurses during care of patients with COVID-19. Subjects and methods: A descriptive exploratory design was utilized on a convenience sample of (80) nurse working at the Critical Care Units affiliated to a specialized isolation hospital in Ismailia City, Egypt, from May to July 2020 using self-administered questionnaire to assess types of conflicts and Rahim Organizational Conflict Inventory-II to assess staff nurses' conflict resolution strategies. Results: All the critical care nurses experienced conflict with significance level in female, due to recurrent contact with infected patients and fear of infection for themselves and their loved ones. Conclusion: Around half of nurses (42.5%) had moderate conflict level, and collaborating was the most common used conflict resolution strategy. Recommendations: Training in conflict resolution strategies during outbreaking terrorism as COVID- 19.